Students Students’ Collaborative Learning Strategy of Think-Pair-Share toward Writing Skill Improvement: (A Study at SMKN 3 Payakumbuh Vocational High School of Fashion Department) - Adzanil Prima Septy; Yollanda Angelina; Fuad Nabil Adzanil (Indra institute Research & Publication, 2025)
This descriptive research aimed to identify the writing skills of students engaged in the Think-Pair-Share (TPS) collaborative learning during English classroom activities. The study focused on 32 students from the Fashion 4 Department at SMKN 3 Payakumbuh Vocational High School, selected through purposive sampling. Data were collected using a set of writing tests, where students collaboratively wrote personal letters being involved in the TPS, and a set of questionnaires to gather feedback from both students and the teacher regarding the implementation of the TPS. The results revealed that students demonstrated strong writing skills in various aspects of personal letter writing, including generic structures, vocabulary usage, grammar, and mechanics. According to the school's Criteria of Learning Mastery (KKM), the students' writing skills were classified as above average, with scores ranging from 75.5 to 94, indicating the effectiveness of the TPS collaborative activities in enhancing writing skills. Based on these findings, several recommendations are proposed for teachers, students, and future researchers. Teachers should continue to facilitate and oversee the use of TPS in writing instruction. Students are encouraged to practice letter-writing extensively, particularly focusing on improving their paragraph writing skills. Future researchers should explore the challenges students face in organizing paragraphs while writing various types of letters.